Facile Fabrication of Concentrated Polymer Brushes with Complex Patterning by Photocontrolled Organocatalyzed Living Radical Polymerization - Wang, Chen‐Gang; Chen, Chen; Sakakibara, Keita; Tsujii, Yoshinobu; Goto, Atsushi (Angewandte Chemie International Edition, 2018)
Photocontrolled surface‐initiated reversible complexation mediated polymerization (photo‐SI‐RCMP) was successfully applied to fabricate concentrated polymer brushes with complex patterning structures. Positive‐type patterned polymer brushes were obtained by photo‐SI‐RCMP under visible light (550(±50) nm) using photomasks. A particularly interesting finding was that negative‐type patterned polymer brushes were also obtainable in a facile manner. A nonspecial UV light (250–385 nm) enabled the preparation of pre‐patterned initiator surfaces in a remarkably short time (1 min), leading to negative‐type patterned polymer brushes. Based on this unique selectivity between visible and UV light, the combination of two patterning techniques enabled the preparation of complex patterned brushes, including diblock copolymers, binary polymers, and functional binary polymers, without multistep immobilization of one or more initiators on the surfaces. Brush up: Positive‐type and negative‐type patterned polymer brushes were obtained by photocontrolled organocatalyzed living radical polymerization in a wavelength‐switchable manner. The two patterning techniques provided a facile method to create complex patterns and functional surfaces.